Sources of academic stress – a study on management students. - Nandamuri, Purna Prabhakar; C H, Gowthami (Journal of Management and Science, 2011)
The objective of this study is to explore the components of academic stress among the post graduate management students. Academic stress among students has long been researched on, and researchers have identified different stressors. The study further tries to make an in-depth investigation into each component of academic stress such as curriculum and instruction, team work related issues, assessment, and placement, to identify the micro issues that are causing stress. Around twelve micro issues have been identified under the curriculum and instruction component while four stressors were prioritized related to team work; five sub issues regarding assessment and three micro issuses under placement components of academic stress. The sample comprises of 500 postgraduate management students from various management institutes spread across the Warangal district of Andhra Pradesh in India. Data was collected through self designed academic stress questionnaire based on previous models available.